Design of an Ultrawide Band Low Noise Microstrip Amplifier Using 3D Sonnet- Based SVRM with Particle Swarm Optimization for Space Applications - Demirel, Salih; Gunes, Filiz; Keskin, Ahmet Kenan (IEEE, 2013)
In this work, a determinististic, efficient design methodology is put forward to design a wide-band, low-noise microstrip amplifier, where the microstrip widths, lengths {(W) over right arrow, (l) over right arrow} of the input/ output matching networks are obtained accurately and fast for a substrate {epsilon(r), h, tan delta} using the cost-effective 3D EM- based Support Vector Regression Machine (SVRM) microstrip model provided that ensuring the stable source Z(S)(omega) and load Z(L)(omega) terminations for the compatible {Noise F(omega) >= F-min(omega), Input VSWR Vi(omega) >= 1, Gain G(Tmin)(omega)>G(T)(omega)>= G(Tmax)(omega), Bandwidth B} quadrates of the employed transistor. The 3D EM- based SVRM microstrip model provides the accurate and fast characterization of the equivalent transmission line in terms of the characteristic impedance Z(0) and the dielectric constant epsilon(eff) within the continuous domain of {0.1mm <= W <= 4.6 mm, 2 <= epsilon(r) <= 10, 0.1mm <= h <= 2.2mm, 2GHz <= f <= 14GHz} in an efficient manner. In the modeling process, the substantial reduction (up to % 64) is obtained utilizing sparseness of SVRM in the number of expensive fine discretization training data with the negligible loss in the predictive accuracy using the quasi-TEM microstrip synthesis formulas as the coarse model that allow to identify the regions of the design space requiring denser sampling. Moreover, the multi-objective amplifier design problem is reduced into the two single-objective design problems of the input(IM)/ output (OM) matching networks to provide the source Z(S)(omega) and load Z(L)(omega) terminations to the transistor, respectively. Finally the design methodology is applied to the design of typical wideband low-noise amplifiers of the transistor NE3512S02 within 3GHz and 8GHz using T-, II- L types of microstrip matching circuits satisfying the maximum gain provided the available minimum noise and a permitted amount of input mismatching at each operation frequency. In the design optimization of the IM/OM networks, a Memetic Algorithm (MA) in which a simple local optimizer called Nelder-Mead (NM) algorithm is used along with the global optimizer Particle Swarm (PSO) algorithm is used. Furthermore, typical T-T designed amplifier is validated using the Circuit Simulator AWR and 3 D EM Simulator SONNET.
Keywords: Support Vector Regression Machine; Microwave Amplifier; Transducer Gain; Noise Figure; Input VSWR; Microstripline; SUPPORT VECTOR SYNTHESIS; PERFORMANCE CHARACTERIZATION; MICROWAVE; Engineering